Comparing Relationship Satisfaction and Body-Image-Related Quality of Life in Pregnant Women with Planned and Unplanned Pregnancies - Razvan-Ionut Daniluc; Marius Craina; Barkha Rani Thakur; Mihaela Prodan; Melania Lavinia Bratu; Ana-Maria Cristina Daescu; George Puenea; Bogdan Niculescu; Rodica Anamaria Negrean (Diseases, 2024)
This comparative cross-sectional study conducted at the “Pius Brinzeu” healthcare center in Timisoara explored the differential impacts of pregnancy planning status on sexual function, body image, and relationship satisfaction among pregnant women. Employing the Female Sexual Function Index (FSFI), Body Esteem Scale for Adolescents and Adults (BESAQ), and the Beck Depression Inventory (BDI-II), the study analyzed responses from 107 participants divided into groups of planned (n = 59, mean age 28.5 ± 5.2) and unplanned (n = 48, mean age 27.3 ± 4.8) pregnancies. In the first trimester, unplanned pregnancies reported higher median scores in desire (4.7 vs. 3.6, p = 0.005), arousal (4.5 vs. 3.8, p = 0.001), and lubrication (4.6 vs. 3.7, p = 0.015) compared to planned pregnancies. Satisfaction scores also favored unplanned pregnancies in the first trimester (4.8 vs. 3.9, p = 0.009). Similar trends were observed in subsequent trimesters, with unplanned pregnancies consistently reporting higher FSFI scores, indicating a robust sexual function. Risk factors significantly associated with sexual dysfunction were a higher BMI in the first trimester (beta coefficient: −0.124, p = 0.019), unmarried civil status (beta coefficient: −0.323, p = 0.045), history of previous abortion (beta coefficient: −0.451, p = 0.012), irregular menstrual cycles (beta coefficient: −0.384, p = 0.026), and rural living area (beta coefficient: −0.278, p = 0.034). Notably, unplanned pregnancy itself was not a significant risk factor for sexual dysfunction (beta coefficient: −0.054, p = 0.095). Regarding relationship dynamics, planned pregnancies exhibited significantly higher satisfaction with partner support (4.1 ± 0.9 vs. 3.7 ± 1.1, p = 0.041) and communication within the couple (4.0 ± 1.0 vs. 3.5 ± 1.2, p = 0.020), whereas unplanned pregnancies reported higher satisfaction with emotional closeness (4.3 ± 0.7 vs. 3.8 ± 1.0, p = 0.004). Concerns about managing professional activities and household chores were significantly more prevalent in the unplanned pregnancy group (62.50% vs. 33.90%, p = 0.014). Unplanned pregnancies demonstrated better initial sexual function but faced greater challenges in relationship satisfaction and managing pregnancy demands. Identifying and addressing the risk factors associated with sexual dysfunction can provide targeted interventions to improve the well-being of pregnant women, regardless of pregnancy planning status.